2016
DOI: 10.1002/chem.201604056
|View full text |Cite
|
Sign up to set email alerts
|

Domino Staudinger/aza‐Wittig/Mannich Reaction: An Approach to Diversity of Di‐ and Tetrahydropyrrole Scaffolds

Abstract: A highly efficient and selective domino reaction producing valuable di- and tetrahydropyrrole-based skeletons from azidoethyl-substituted CH-acids and (thio)carbonyl compounds has been developed. By involving the additional functional groups in starting compounds into the domino reaction or postmodification of the primary reaction products, the simple construction of the pharmaceutically relevant three- and polycyclic azaheterocyclic scaffolds was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…These results not only lie in the wide scenario of the heterocyclic scaffolds obtainable through tandem Staudinger/aza-Wittig sequence [24,25,37,38,39,40,41], but the concurrent presence of reactive functionalities in the target compounds 5a – k ensures post-modifications in view of heterobicyclic structures. In fact, the tautomerism thionoamide/thioloimide permits the introduction of a further element of diversity at the sulfur atom producing imidazole derivatives suitable to be combined with the useful 1-amino-Boc protected group [42] directly installed by this approach, as for 5a , 5c – f, 5k .…”
Section: Resultsmentioning
confidence: 99%
“…These results not only lie in the wide scenario of the heterocyclic scaffolds obtainable through tandem Staudinger/aza-Wittig sequence [24,25,37,38,39,40,41], but the concurrent presence of reactive functionalities in the target compounds 5a – k ensures post-modifications in view of heterobicyclic structures. In fact, the tautomerism thionoamide/thioloimide permits the introduction of a further element of diversity at the sulfur atom producing imidazole derivatives suitable to be combined with the useful 1-amino-Boc protected group [42] directly installed by this approach, as for 5a , 5c – f, 5k .…”
Section: Resultsmentioning
confidence: 99%
“…Such behavior of ambident thiocyanate ion differs crucially from the typical reactivity of this nucleophile with saturated carbon atoms when S ‐attack proceeds predominantly or exclusively [12] . It should be noted that our previous two‐step transformation of cyclopropanes 1 to pyrrolidine‐2‐thiones 2 required prolonged heating and tremendous combined reaction times, provided much lower yields and involved toxic reagents [13] …”
Section: Introductionmentioning
confidence: 88%
“…Based on multiple reports that S-attack of thiocyanate is kinetically preferred in both S N 2a nd S N 1r eactions, [12,31] the alternative mechanism including an initial formation of thiocyanate B followed by its isomerization to A could also be supposed (Scheme 4, path b). Thec yclization of intermediate A to the target pyrrolidine-2-thione 2 [13] is akey step for both possible mechanisms.O ur failure to identify thiocyanates B in reaction mixtures supports path a,but cannot be considered as an argument against the alternative route.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[165][166][167] The method for the synthesis of 213 relied upon nucleophilic ring opening of DA cyclopropanes 212 activated with aryl-, hetaryl-, and alkenyl-substituents as the EDG (R) and ester, acyl, nitro, and cyano groups as EWG with the azide ion (Scheme 120). 165 The experimental data showed that the reaction proceeded via an S N 2-like mechanism with reversal of configuration at the electrophilic center of cyclopropane 212.…”
Section: Scheme 119mentioning
confidence: 99%